2006
DOI: 10.1186/1471-2334-6-136
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early death in a cohort of Ethiopian patients treated with HAART

Abstract: Background: HAART has improved the survival of HIV infected patients. However, compared to patients in high-income countries, patients in resource-poor countries have higher mortality rates. Our objective was to identify independent risk factors for death in Ethiopian patients treated with HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
67
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 24 publications
15
67
3
Order By: Relevance
“…This higher mortality rate was similar with studies conducted in different Africa countries [5,7,[9][10][11][12][13]. The early deaths may reflect the late initiation of ART with the advanced clinical stage and severely compromised status of CD4 cell counts (<50 cells/ µl).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This higher mortality rate was similar with studies conducted in different Africa countries [5,7,[9][10][11][12][13]. The early deaths may reflect the late initiation of ART with the advanced clinical stage and severely compromised status of CD4 cell counts (<50 cells/ µl).…”
Section: Discussionsupporting
confidence: 76%
“…Hence, Successful implementation of such initiatives needs scientific evidence generated in the appropriate settings [7].…”
Section: Introductionmentioning
confidence: 99%
“…The studies from limited setting also reported similar results (Jerene et al, 2006). Van der Sande et al (2004) had advocated that BMI at the time of HIV diagnosis is a strong and independent predictor of survival.…”
Section: Discussionsupporting
confidence: 67%
“…To our knowledge hemoglobin has never shown to predict mortality of patients on ART in India, further studies are needed to confirm our findings. Baseline hemoglobin level can be used as a simple and practical tool for initial risk assessment in the absence of CD4 cell count and viral load, as was identified in earlier studies by Johannessen et al (2008) in Tanzania, Jerene et al (2006) in Ethopia and Mocroft et al (1999) in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation